Valuation of Forest Non-Market Values : An empirical study in Northern Sweden - Otterbeck, Daniel; Lundstedt, Fredrik (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2017)
The purpose of this study was to investigate the Willingness to Pay (WTP) of conserving a ten hectares forest area in Rutvik, amongst the population of Luleå municipality. Furthermore, the study investigated the factors influencing the WTP and its impact on a Faustmann-Hartman rotation period. The tested influential factors were both socio-economic and attitudes towards use values and non-use vales that a forest stand can provide the society. The study used an empirical approach, were a survey was created using a Contingent Valuation Method (CVM). The survey consisted of three parts, where the first part asked the respondents general questions, the second part let the respondent rate different type of forest values and finally a last part where an open-ended question asked the respondents of their maximum WTP. The results indicated that the mean WTP was equal to 15.9 SEK for the total forest area. The results also demonstrated that income had a significant positive impact on WTP and that living nearer the targeted forest gave a higher probability of having a WTP. The only service that indicated significant result was altruistic values, which value had a positive impact on the WTP. It also indicated that the researched WTP extended the traditional Faustmann rotation formula from 56 to 58 years for pine and 75 to 78 years for spruce.